Integrating Mangenta Local Wisdom into Pesantren Leadership:An Empirical Model of Educational Transformation - Ahmadi, Ahmadi; Azis, Abdul; Ajahari, Ajahari; Syuhud, Syuhud; Wasehudin, Wasehudin (SCAD Independent, 2026)
Islamic boarding school (pesantren) leadership is increasingly required to respond to contemporary educational challenges while sustaining deeply rooted religious, cultural, and institutional traditions. However, integrative leadership models that systematically bridge indigenous wisdom with modern education remain underexplored. This study examines the development of an adaptive pesantren leadership framework by integrating the Mangenta philosophy as indigenous local knowledge with critical pedagogy and systematic transformation. Employing a quantitative research design, data were collected through structured surveys administered to kyai, teachers, and educational practitioners in pesantren settings and analyzed using Structural Equation Modeling (SEM). Reliability and construct validity were confirmed through Cronbach’s alpha and Average Variance Extracted (AVE). The findings reveal that local knowledge exerts a strong influence on Mangenta philosophy, while critical pedagogy significantly mediates the internalization of local wisdom into leadership practices. Systematic transformation contributes as a supporting institutional condition that facilitates adaptation without undermining philosophical coherence. These results demonstrate that Mangenta-based local wisdom, when critically mediated and institutionally supported, forms a culturally grounded and adaptive pesantren leadership model. The study contributes to Islamic educational leadership scholarship by offering an empirically validated, context-sensitive framework that harmonizes tradition and innovation within faith-based educational institutions.